2016
DOI: 10.21037/atm.2016.09.30
|View full text |Cite
|
Sign up to set email alerts
|

PAX1 and SOX1 methylation as an initial screening method for cervical cancer: a meta-analysis of individual studies in Asians

Abstract: Background: Epigenetic alterations of gene or DNA methylation have been highlighted as promising biomarkers for early cervical cancer screening. Herein, we evaluated the diagnostic performance of paired boxed gene 1 (PAX1) and sex determining region Y-box 1 (SOX1) methylation for cervical cancer detection.Methods: Eligible studies were retrieved by searching the electronic databases. Study quality was assessed according to the Quality Assessment of Diagnostic Accuracy Studies (QUADAS) checklist. The bivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…Another study reported PAX1 expression‐inducing tumor formation following subcutaneous injection of cultured cells expressing PAX1 into nude mice (Maulbecker & Gruss, ). Additionally, other studies showed that methylation of CpG islands in the PAX1 promoter region regulates cervical neoplasia (Chen et al, ; Kan et al, ), resulting in their characterization of PAX1 as a tumor suppressor gene. Although PAX1 functions have been hypothesized based on phenotypic outcomes associated with knockout models, PAX1 molecular functions and target genes remain largely unknown.…”
Section: Potential Mechanisms Of Pax1 Methylationmentioning
confidence: 99%
“…Another study reported PAX1 expression‐inducing tumor formation following subcutaneous injection of cultured cells expressing PAX1 into nude mice (Maulbecker & Gruss, ). Additionally, other studies showed that methylation of CpG islands in the PAX1 promoter region regulates cervical neoplasia (Chen et al, ; Kan et al, ), resulting in their characterization of PAX1 as a tumor suppressor gene. Although PAX1 functions have been hypothesized based on phenotypic outcomes associated with knockout models, PAX1 molecular functions and target genes remain largely unknown.…”
Section: Potential Mechanisms Of Pax1 Methylationmentioning
confidence: 99%
“…13 The genes SOX1 and PAX1 have been reported as potential methylation biomarkers and studies have demonstrated their promise in the detection of cervical intraepithelial neoplasms (CIN) grade 3 and worse lesions (CIN3+). [15][16][17][18] However, the published data were highly heterogeneous. No methylation markers can yet be utilized in cervical cancer screening or triage settings.…”
Section: Introductionmentioning
confidence: 99%
“…18 Related studies show that methylation of PAX1 promoter region CpG islands may lead to or promote the occurrence of cervical cancer. 18,25 Current meta-analysis studies of PAX1 gene methylation mainly focused on normal and cervical cancer, and little analysis was available, regarding PAX1 gene methylation in progression of CIN. This meta-analysis, which combined results from 7 studies of 1055 patients, explores the association of PAX1 methylation with the progression of CIN.…”
Section: Discussionmentioning
confidence: 99%